2021
DOI: 10.3390/plants10112450
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Weed-Suppressing Potential of Cotton Chromosome Substitution Lines Using the Stair-Step Assay

Abstract: Palmer amaranth is a problematic common weed species, especially in cotton. With the wide use of chemical herbicide and herbicide-tolerant transgenic cotton lines, Palmer amaranth populations have developed tolerance to commonly used herbicides. It is imperative to develop alternative weed control methods to slow the evolution of herbicide-resistant weed populations and provide new strategies for weed management. Eleven chromosome substitution (CS) cotton lines (CS-B26lo, CS-T17, CS-B16-15, CS-B17-11, CS-B12, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…PCA and clustering have been used to group allelopathic weed-suppressive cotton lines based on their weed-suppressive potential, which can aid in gaining a deeper insight into breeding material for crop enhancement (Fuller et al, 2021) [2]. Similarly, the grouping of rice cultivars by Schumaker et al (2020) [19] and sweet potato varieties by Singh et al (2022) [25] has been carried out using similar strategies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PCA and clustering have been used to group allelopathic weed-suppressive cotton lines based on their weed-suppressive potential, which can aid in gaining a deeper insight into breeding material for crop enhancement (Fuller et al, 2021) [2]. Similarly, the grouping of rice cultivars by Schumaker et al (2020) [19] and sweet potato varieties by Singh et al (2022) [25] has been carried out using similar strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Providing approximately 35 percent of global cotton exports in recent years, the United States is the world’s leading cotton exporter. Among the U.S. States, Texas is the largest producer, accounting for approximately 40 percent of U.S. cotton production, with other top producers being Georgia, Mississippi, and Arkansas [ 2 ]. The plant is also a known source of valuable chemical compounds, including fatty acids, lipids, carbohydrates, and phenolics [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to preliminary studies on cotton allelopathy [39], cotton root showed significant quantities of four phenolic chemicals, including p-hydroxybenzoic acid, ferulic acid, gallic acid, and vanillin. A greenhouse study was conducted using eleven cotton chromosome substitution (CS) lines for allelopathy screening against Palmer amaranth (Amaranthus palmeri) (PA) [40]. The cotton lines were tested using a modified stair-step assay.…”
Section: Cotton Allelopathymentioning
confidence: 99%